The firefly genus Pteroptyx Olivier revisited (Coleoptera: Lampyridae: Luciolinae) - Jusoh, Wan F. A.; Ballantyne, Lesley; Lambkin, Christine L.; Hashim, Nor Rasidah; Wahlberg, Niklas (Zootaxa, 2018)
The synchronous firefly genus Pteroptyx Olivier is reassessed from morphological, molecular, and habitat perspectives in Malaysia, and includes some reliably associated females described from morphological features and internal female reproductive anatomy. Phylogenetic analyses using combined morphological and molecular data (where available) for 158 taxa supported all the major features of the existing taxonomic categories within the Indopacific Luciolinae. They revealed a distinct Pteroptyx clade as a morphologically variable genus with Poluninius selangoriensis Ballantyne being newly synonymised with Luciola testacea Motschulsky, the type species, which is redescribed from the type series. Pteroptyx gelasina Ballantyne was shown to be distinct and three of the four morphological subdivisions within Pteroptyx malaccae (Gorham) considered useful. A new species Pt. balingiana Jusoh sp. nov. is described from Sarawak. A second specimen of Pt. gombakia Ballantyne is described and figured.        Some females were reliably associated with identified males by molecular data, but investigation of their morphology showed consistent features that were for the most part not useful for species delineation, which still relies on association with the males and colour patterns. All females investigated had bursa plates.Habitat details for most Pteroptyx revealed an association with a riparian environment likely to support mangroves but not necessarily an obligatory association with mangroves or any particular species. Pteroptyx galbina Jusoh was found up to 30 km from the sea, and Pt. bearni Olivier displays in a variety of flowering plants alongside rivers, including mangroves.Keys to species and diagnoses of all species with coloured plates are given.